2017
DOI: 10.1371/journal.pgen.1006715
|View full text |Cite
|
Sign up to set email alerts
|

Loss of SLC9A3 decreases CFTR protein and causes obstructed azoospermia in mice

Abstract: Mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene cause cystic fibrosis (CF) and are associated with congenital bilateral absence of the vas deferens (CBAVD), which is the major cause of infertility in male patients with CF. However, most Taiwanese patients with CBAVD do not carry major CFTR mutations. Some patients have a single copy deletion of the solute carrier family 9 isoform 3 (SLC9A3) gene. SLC9A3 is a Na+/H+ exchanger, and depleted Slc9a3 in male mice causes infertility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 51 publications
2
37
0
Order By: Relevance
“…SLC26A3 is known to interact with the CFTR channel, and a physical and functional interaction between SLC26A3 and the sodium/hydrogen antiporter 3, NHE3, was also reported in both the intestine and in the male reproductive system (Hihnala et al, ; Lamprecht et al, ; Melvin, Park, Richardson, Schultheis, & Shull, ; Musch, Arvans, Wu, & Chang, ). Importantly, Wang and collaborators recently showed that NHE3‐deficient mice display several defects in the ultrastructure of the epididymis and the vas deferens, as well as significant reduction of CFTR protein levels in these structures, ultimately leading to male infertility (Wang et al, ). These results corroborate the hypothesis of a functional multi‐channel protein complex, CFTR/SLC26A3/NHE3, involved in the regulation of ion microenvironment that would be required for normal cytoarchitecture of the male reproductive tract.…”
Section: Discussionmentioning
confidence: 99%
“…SLC26A3 is known to interact with the CFTR channel, and a physical and functional interaction between SLC26A3 and the sodium/hydrogen antiporter 3, NHE3, was also reported in both the intestine and in the male reproductive system (Hihnala et al, ; Lamprecht et al, ; Melvin, Park, Richardson, Schultheis, & Shull, ; Musch, Arvans, Wu, & Chang, ). Importantly, Wang and collaborators recently showed that NHE3‐deficient mice display several defects in the ultrastructure of the epididymis and the vas deferens, as well as significant reduction of CFTR protein levels in these structures, ultimately leading to male infertility (Wang et al, ). These results corroborate the hypothesis of a functional multi‐channel protein complex, CFTR/SLC26A3/NHE3, involved in the regulation of ion microenvironment that would be required for normal cytoarchitecture of the male reproductive tract.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, these authors showed that the adult male mouse SLC9A3-/develops obstructive azoospermia due to structural and functional abnormalities of the efferent ductules with long-term progressive atrophy of the vas deferens and seminal vesicles (Wu et al 2019;Chiang et al 2019). Remarkably, authors observed a drastic decrease in CFTR in the epididymis and vas deferens in these SLC9A3-KO mice suggesting interdependent roles of the two genes in iCBAVD determinism (Wang et al 2017). However, despite these very enlightening observations on the role of SLC9A3 in the physiology of the reproductive tract of male mice, the relationship between the loss of a copy of this gene and iCBAVD in humans is still poorly understood.…”
Section: Other Mutationsmentioning
confidence: 96%
“…SLC9A3 is one of nine plasma membrane Na + /H + exchangers (SLC9A1-9) and is expressed on the apical membranes of the intestinal epithelium, renal proximal tubule, epididymis, and vas deferens [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. The widely known functions of SLC9A3 are ion homeostasis regulation through Na + and water absorption, and it often functionally couples with transepithelial Cl − /HCO 3 − exchangers in the intestine [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Through oligonucleotide array-based comparative genomic hybridization (array-CGH), we identified the loss of one Slc9a3 allele in 28.57% of Taiwanese men with CBAVD [ 23 ]. However, loss of SLC9A3 causes obstructive azoospermia and testicular atrophy [ 6 ]. Colleagues’ and our own studies have indicated that Slc9a3 −/− adult male mice are completely infertile compared with wild-type (WT) and heterozygous mice [ 6 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation